Diagnostic Value and Prognostic Evaluation of Autophagy-Related Protein Expression Level in Sepsis Complicated with Acute Respiratory Distress Syndrome. (25th March 2022) - Xu, Jia-Li; Yu, Xue-Lu; Yao, Xiao-Qin; Xu, Li-Hong; Jing, Mei
Abstract : Objective . To explore the diagnostic value and prognostic evaluation of the autophagy-related protein expression level among patients with sepsis comorbid with acute respiratory distress syndrome. Methods . A total of 182 sepsis patients were admitted to Naval Medical Center from March 2016 to April 2020 and divided into the acute respiratory distress syndrome and non-ARDS groups. Immunoblotting was employed to identify the expression of autophagy-associated protein from participants' peripheral blood mononuclear cells. Multivariate linear regression analysis was used to examine the association between mortality and the protein expression in sepsis complicated with acute respiratory distress syndrome. Results . Among the 182 patients with sepsis included in this study, 82 patients had acute respiratory distress syndrome and 100 patients did not have acute respiratory distress syndrome. We observed that microtubule-related protein 1A/1B LC3II, Beclin-1, RAB7, and LAMP2 protein expression was significantly decreased in septic patients with ARDS, and p62 was significantly increased. Further receiver operating characteristic curve analysis showed that autophagy-related proteins had a high recognition ability in sepsis complicated with acute respiratory distress syndrome. LAMP2 protein was the best among them, and its specificity was up to 91.46%. In this study, 38 of the 82 patients with sepsis complicated with acute respiratory distress syndrome died, with a mortality rate of 46.34%. We found that the autophagy level was further inhibited in the patients with death, LC3II, Beclin-1, and RAB7. However, the lysosomal-associated membrane protein 2 levels in the survival patients were remarkably higher than that in the dead patients. In addition, the p62 level was lower in survival patients as well. Our results indicated age and SOFA score were the independent risk factors for mortality in septic patients with acute respiratory distress syndrome. Conclusion . The autophagy level is significantly inhibited in septic patients with acute respiratory distress syndrome, and autophagy-associated proteins LC3II, Beclin-1, RAB7, LAMP2, and p62 have good value for the diagnosis and prognosis evaluation of sepsis comorbid with acute respiratory distress syndrome.